The Importance of Vitamin D and Magnesium in Athletes - Dominguez, L. J.; Veronese, N.; Ragusa, F. S.; Baio, S. M.; Sgrò, F.; Russo, A.; Battaglia, G.; Bianco, A.; Barbagallo, M. (Nutrients, 2025)
Vitamin D and magnesium are essential nutrients that play key roles in an athlete`s performance, recovery, and overall health. Vitamin D is crucial for bone health (aiding calcium absorption and preventing stress fractures), muscle function (preventing weakness and injury), and reducing respiratory infections. Magnesium is fundamental in muscle function, adenosine triphosphate production for muscle contraction, electrolyte balance, bone strength, and cardiovascular health. The magnesium requirement of healthy adults is estimated at 300-400 mg/day, but there is evidence that athletes may have higher magnesium needs compared to sedentary persons. Magnesium and vitamin D are closely linked—vitamin D aids magnesium absorption, while magnesium is vital for vitamin D synthesis, transport, and activation. Given their importance in athletes, this article explores their functions, interactions, and the effects of deficiencies and supplementation in athletic populations.